Effect of chlorogenic acid on lipid metabolism in 3T3-L1 cells induced by oxidative stress. (February 2023) - Liu, Libo; Zhang, Chenyi; Zhai, Min; Yu, Tianshu; Pei, Mengqi; Du, Peng; Li, Aili; Yan, Jiayi; Li, Chun; Zhang, Guofang
Abstract: Chlorogenic acid (CGA), a phenolic acid compound found in a variety of natural plants, has strong antioxidant capacity. In this study, we aimed to investigate the effects of CGA on differentiation and lipid metabolism of 3T3-L1 cells, as well as its protective effect against cellular oxidative stress induced by H2 O2 . We found that CGA can reduce the accumulation of intracellular ROS and attenuate the production of inflammatory cytokines TNF-α under oxidative stress. CGA treatment significantly inhibited preadipocytes differentiation and lipid accumulation in 3T3-L1 cells. Our results suggest that CGA may regulate lipid metabolism by reducing the expression of differentiation-related genes and inhibiting triacylglyceride synthesis. The findings of this study support CGA as a potential therapeutic agent for obesity. The effects of CGA and its metabolites in vivo should be investigated to further support its application in functional foods.